New species and records of Galumnidae (Acari, Oribatida) from the Philippines - Ermilov, Sergey G.; Corpuz-Raros, Leonila (Zootaxa, 2016)
We collected 19 species in eight genera of poronotic oribatid mites of the family Galumnidae from the Philippines. Five species, Galumna (Cosmogalumna) areticulata Ermilov, Sandmann, Klarner, Widyastuti & Scheu, 2015, G. (Neogalumna) tolstikovi Ermiov & Anichkin, 2014, Pergalumna (Pergalumna) crassipora Mahunka, 1995, P. (Pergalumna) margaritata Mahunka, 1989 and Trichogalumna nipponica (Aoki, 1966), the subgenus Galumna (Neogalumna) and the genus Trichogalumna are recorded for the first time in the fauna of this country. Three new species of the genera Pergalumna, Setogalumna and Trichogalumna are described. Pergalumna (Pergalumna) capualensis sp. nov. differs from P. (Pergalumna) bimaculata Hammer, 1973 and P. (Pergalumna) remota (Hammer, 1968) by the larger body length and the presence of strong teeth on prodorsum. Setogalumna minisetosa sp. nov. differs from S. luzonica Ermilov & Corpuz-Raros, 2015 by the smaller body size, the presence of minute interlamellar and notogastral setae, median pore and elongated notogastral porose areas A3, and the absence of notogastral porose areas A2. Trichogalumna interlamellaris sp. nov. differs from T. seminuda Balogh, 1960 by the larger body size, the presence of anterior notogastral margin and small bothridial heads, the absence of notogastral porose areas A2, and the localization of adanal setae ad3. Supplementary description of Pergalumna (Pergalumna) crassipora Mahunka, 1995 is presented.